2023
DOI: 10.1021/acs.langmuir.3c00091
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surface Roughness, Nanostructure, and Wetting on Bacterial Adhesion

Abstract: Bacterial fouling is a persistent problem causing the deterioration and failure of functional surfaces for industrial equipment/components; numerous human, animal, and plant infections/diseases; and energy waste due to the inefficiencies at internal and external geometries of transport systems. This work gains new insights into the effect of surface roughness on bacterial fouling by systematically studying bacterial adhesion on model hydrophobic (methyl-terminated) surfaces with roughness scales spanning from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 92 publications
3
14
1
Order By: Relevance
“…Various surface properties of materials are known to influence microbial adhesion. Surface roughness, surface energy, and the resulting wettability of substrates have been found to have a significant impact on microbial adhesion. Additionally, the cell surface hydrophobicity (CSH) and physicochemical interactions, such as van der Waals interactions, electrostatic interactions, and acid–base interactions, that occur on the microbial surface also have a substantial influence on the initial microbial adhesion. After addition of NCs to PMMA, when DW and EG were dropped onto the specimen surface, both exhibited an increase in contact angle. Based on these results, it was confirmed that the addition of NCs to PMMA made the surface hydrophobic, particularly at 4 wt %, with a significantly increased antiadhesion activity of C.…”
Section: Discussionmentioning
confidence: 99%
“…Various surface properties of materials are known to influence microbial adhesion. Surface roughness, surface energy, and the resulting wettability of substrates have been found to have a significant impact on microbial adhesion. Additionally, the cell surface hydrophobicity (CSH) and physicochemical interactions, such as van der Waals interactions, electrostatic interactions, and acid–base interactions, that occur on the microbial surface also have a substantial influence on the initial microbial adhesion. After addition of NCs to PMMA, when DW and EG were dropped onto the specimen surface, both exhibited an increase in contact angle. Based on these results, it was confirmed that the addition of NCs to PMMA made the surface hydrophobic, particularly at 4 wt %, with a significantly increased antiadhesion activity of C.…”
Section: Discussionmentioning
confidence: 99%
“…Upon completion of the growth period, the stencil is removed, leaving the desired bacterial patterns on the surface. Elastomeric PDMS is commonly employed for stencil patterning due to its softness, cost-effectiveness, and flexible nature. , Taking advantage of the flexibility of PDMS stencils, it becomes feasible to pattern bacteria on various substrate surfaces, including those that are rough, corrugated, topographically textured, or even curved . However, nonspecific adhesion of bacterial cells may lead to pattern distortion.…”
Section: Bacterial Patterning Strategiesmentioning
confidence: 99%
“…Accordingly, preparing substrates using biobased materials to achieve green and sustainable solutions is gaining attention . Furthermore, the fabrication of substrates with antimicrobial and antiviral characteristics is getting attention due to the modern-day problem of multidrug-resistant bacteria. Furthermore, there is a need for methods that result in durable surface-engineered substrates. For instance, the durability and stability of widely used self-cleaning fluoropolymer TiO 2 superhydrophilic coatings are greatly influenced by time of ultraviolet exposure, followed by the amount of the polymer in the composition used .…”
Section: Current Challenges and Future Directionsmentioning
confidence: 99%